2015
DOI: 10.3390/ijerph121215027
|View full text |Cite
|
Sign up to set email alerts
|

Active Travel by Built Environment and Lifecycle Stage: Case Study of Osaka Metropolitan Area

Abstract: Active travel can contribute to physical activity achieved over a day. Previous studies have examined active travel associated with trips in various western countries, but few studies have examined this question for the Asian context. Japan has high levels of cycling, walking and public transport, similar to The Netherlands. Most studies have focused either on children or on adults separately, however, having children in a household will change the travel needs and wants of that household. Thus, here a househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…Similarly to previous studies in the U.K. ( Hutchinson et al, 2014 ), Australia ( Heesch et al, 2015 ), North America ( Waygood et al, 2015 ) and the Netherlands ( Scheepers et al, 2013 ) we found that those living in urban areas were more likely to actively travel a journey stage than those living in rural areas. In addition, our results highlighted that, although there was a difference in active travel between urban/rural areas, when adjusted for age, sex, employment and socioeconomic status the difference was not significant.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly to previous studies in the U.K. ( Hutchinson et al, 2014 ), Australia ( Heesch et al, 2015 ), North America ( Waygood et al, 2015 ) and the Netherlands ( Scheepers et al, 2013 ) we found that those living in urban areas were more likely to actively travel a journey stage than those living in rural areas. In addition, our results highlighted that, although there was a difference in active travel between urban/rural areas, when adjusted for age, sex, employment and socioeconomic status the difference was not significant.…”
Section: Discussionsupporting
confidence: 87%
“…Life stages heavily interact with engagement in AT, including mode (walking or cycling). AT behaviour often reflects circumstances such as household income, number of children, employment, residence options and dozens of other factors (Barnes et al, 2016;Bonham and Wilson, 2012;Clark et al, 2014;Guell et al, 2012;Jones et al, 2015;Susilo et al, 2018;Waygood et al, 2015). Many of these factors highly correlate with sex and age, which suggests that best strategies to promote AT may link to age and sex of target participants.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is not the purpose of this paper to discuss the sources and social implications of these findings. Nonetheless, let us point out that an urban development based on low‐density residential sprawl is likely to generate undesirable effects such as an increase in greenhouse gas emissions (Hankey and Marshall ), hinder social cohesion and promote polarization (Walks ), and prompt public health concerns (Ewing et al ; Waygood et al ).…”
Section: Resultsmentioning
confidence: 99%